1998
DOI: 10.1029/98jd00458
|View full text |Cite
|
Sign up to set email alerts
|

Physical, chemical, and optical properties of regional hazes dominated by smoke in Brazil

Abstract: Abstract. Gas and particle measurements are described for optically thick regional hazes, dominated by aged smoke from biomass buming, in the cermdo and rain forested regions of Brazil. The hazes tended to be evenly mixed from the surface to the trade wind inversion at 34 km in altitude. The properties of aged gases and particles in the regional hazes were significantly different from those of young smoke (<4 min old). As the smoke aged, the total amount of carbon in non-methane hydrocarbon species (C Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

40
420
8
4

Year Published

2005
2005
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 473 publications
(472 citation statements)
references
References 50 publications
40
420
8
4
Order By: Relevance
“…Our results showed higher values for O3 mixing ratios, ranging from 10 to 75 ppbv in FP and 20 to 70 ppbv in AP. Agreeing with SAMBBA results, Reid et al (1998) found O3 mixing ratios ranging from 60 to 100 ppbv during SCAR-B experiment in the 1995 dry season, and Kaufman et al (1992) found similar levels of O3 in a forest site in Amazonia during BASE A (Table 3). …”
Section: Ambient Distributions Of Co Nox and O3mentioning
confidence: 65%
“…Our results showed higher values for O3 mixing ratios, ranging from 10 to 75 ppbv in FP and 20 to 70 ppbv in AP. Agreeing with SAMBBA results, Reid et al (1998) found O3 mixing ratios ranging from 60 to 100 ppbv during SCAR-B experiment in the 1995 dry season, and Kaufman et al (1992) found similar levels of O3 in a forest site in Amazonia during BASE A (Table 3). …”
Section: Ambient Distributions Of Co Nox and O3mentioning
confidence: 65%
“…In practice, a value of about 10 m 2 g −1 is typically used to derive BC e from absorption measurements. However, the range of values for α ATN reported in the literature is between about 1 to 30 m 2 g −1 (Liousse et al, 1993;Chylek et al, 1995;Liousse et al, 1995;Colbeck et al, 1997;Petzold et al, 1997;Martins et al, 1998a;Moosmüller et al, 1998;Reid et al, 1998a;Fuller et al, 1999;Kopp et al, 1999;Lavanchy et al, 1999;Dillner et al, 2001;Sharma et al, 2002;Lim et al, 2003;Schnaiter et al, 2003). This range is so large because, in addition to the inherent variability of α abs , α ATN is affected by experimental bias.…”
Section: Problems Related To the Relationship Of C Soot Mass Concentrmentioning
confidence: 73%
“…Biomass burning is not the only source of oxalate but it is clearly the dominating one. In biomass burning aerosols concentrations may be in the order of several µg m −3 (e.g., Reid et al, 1998) whereas in clean marine aerosols concentrations are some ng m −3 . It is not clear whether they oxalate is emitted directly or produced photochemically in the atmosphere from gaseous precursors (Neusüβ et al, 2002).…”
Section: Saharan Dust and Biomass Burningmentioning
confidence: 99%